Pemenuhan Hak Atas Kebutuhan Seksual Warga Binaan Pemasyarakatan - Nugroho, Okky Chahyo (Jurnal HAM, 2015)
Protection of Human Rights (HAM) in a correctional environment increasingly viable echoed today, in line with international human rights normativity that constantly integrated into the national system of Indonesia. This directly impacts the progresitvitas protection of individuals, in this case prisoners, during a period of coaching in the penitentiary. Nevertheless, it still remains a matter of public discussion is related to the fulfillment of the right to sexual needs for prisoners. Of course, many things that need to be considered in the design of the mechanism of the right to sexual needs of prisoners. It is intended to determine how states apply the principle of proportionality in the context of the right to sexual needs of prisoners. Through a qualitative approach is accompanied by interviews, this study is expected to eventually be the subject of penal policy formulation to be more advanced aspects of the protection of civil rights of the individual, taking into account the security aspects and the social order of society. This study found a significant relationship between the right to sexual needs against sexual perversion and crime and divorce rates inmates. Nonetheless, found an interesting phenomenon that shows the differences between inmates paradigm sexual needs of men and women, and yet there is a setting that specifically regulates sexual fulfillment for inmates. Therefore, the fulfillment of sexual needs as rights of prisoners should be regulated by a variety of restrictions and review of institutions adhering to the values of society and does not injure the value of public justice.